2017
DOI: 10.1080/03601234.2017.1371551
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration and half-life of quinalphos pesticide in rice-fish integration system in the Mekong Delta, Vietnam

Abstract: In order to determine the distribution and enable the elimination of quinalphos, a popular active pesticide compound used in the Mekong Delta, an experiment was set up in a rice-fish integration system in Can Tho City, Vietnam. Fish was stocked into the field when the rice was two-months old. Quinalphos was applied twice in doses of 42.5 g per 1000 m. Water, fish and sediment samples were collected at time intervals and analyzed by a Gas Chromatography Electron Capture Detector system. The results show that qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, CUPs are not transient or harmless in the environment. These pesticides are being increasingly studied because they have been found to have distinct half-lives in natural conditions from previously expected through laboratory experiments (Gouin, Cousins, et al, 2004;Ruggirello et al, 2010;Thinh et al, 2018) and have been detected in remote areas such as mountains, lakes, groundwater, and polar regions beyond the direct influence of human activities (Guida et al, 2018;Kurt-Karakus et al, 2010;Luek et al, 2017;Muir et al, 2004;Westgate et al, 2013;Yao et al, 2007). Furthermore, the bioaccumulation of CUPs and their passage through food chains pose potential risks to human health (Dittmann et al, 2012;Macdonald et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, CUPs are not transient or harmless in the environment. These pesticides are being increasingly studied because they have been found to have distinct half-lives in natural conditions from previously expected through laboratory experiments (Gouin, Cousins, et al, 2004;Ruggirello et al, 2010;Thinh et al, 2018) and have been detected in remote areas such as mountains, lakes, groundwater, and polar regions beyond the direct influence of human activities (Guida et al, 2018;Kurt-Karakus et al, 2010;Luek et al, 2017;Muir et al, 2004;Westgate et al, 2013;Yao et al, 2007). Furthermore, the bioaccumulation of CUPs and their passage through food chains pose potential risks to human health (Dittmann et al, 2012;Macdonald et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The clearance rate constants (K 2 ) of pyraoxystrobin in zebrafish were 0.5795 and 0.4721, and the half-lives were 3.84 and 3.33 d, respectively. At present, studies have reported that quinalphos-carp (half-life of 1.9 d) and silver barb (half-life of 2.5 d) [22], carbofuran has a half-life of 1.63 d in zebrafish), and carbofuran in zebrafish has a half-life of 3.33 d [23], the half-life of fipronil in rainbow trout is 0.61 d [24], and the half-life of fipronil in loach is 1.8-3.8 d [25], which is close to the results of this study.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Rahman and Islam 149 observed the effective use of quinalphos to control parasitic infestations in commercial aquaculture in Bangladesh and the limited bioaccumulation of the drug with transient alteration in the density of natural zooplankton and other aquatic benthos in the pond environment. Earlier, the elimination half‐life of quinalphos was reported to be 2.5 days in silver barb ( Barbonymus gonionotus ) and 1.9 days in common carp ( Cyprinus carpio ) 150 . Though degradation of this compound through photolysis and hydrolysis in the environment has been reported, it is essential to advise farmers to shift to alternate and safer antiparasitic agents due to some of the food safety concerns 151,152 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier, the elimination half-life of quinalphos was reported to be 2.5 days in silver barb (Barbonymus gonionotus) and 1.9 days in common carp (Cyprinus carpio). 150 Though degradation of this compound through photolysis and hydrolysis in the environment has been reported, it is essential to advise farmers to shift to alternate and safer antiparasitic agents due to some of the food safety concerns. 151,152 Albendazole a benzimidazole carbamate, is widely used to treat gastrointestinal parasite infections in animals with MRL of 100-1000 μg kg À1 .…”
Section: Chemicals Biologicals and Vmps Used In Indian Aquaculturementioning
confidence: 99%